Legal Impact for Health Facilities in Filling in Inauthentic Birth Certificate Data - Idayati, Ns. Dewa Ayu Made; Manuaba, Ida Bagus Gede Fajar; Purwanto, I Wayan Novy (Dinasti Research, 2025)
This research is about the legal impact for health facilities in filling out inauthentic birth certificate data. A birth certificate is a vital official document in population administration, serving as proof of birth and the basis for access to public services. However, inauthentic data entry can occur due to human error or intent to deceive, which has the potential to have significant legal impacts for the health facilities (faskes) that issue it. This research aims to examine the legal impacts faced by health facilities due to filling out inauthentic birth certificate data and examine the legal enforcement process for health facilities that issue birth certificates with inaccurate data. This research will analyze the legal impact on health facilities regarding filling out inauthentic birth certificate data using a normative juridical legal approach. The focus is on regulations governing population administration and the legal responsibilities of health facilities. The methods used include regulatory studies, jurisprudential studies. Findings show that legal impacts include administrative sanctions, revocation of operational permits, and lawsuits, while the law enforcement process involves monitoring, investigation, data verification, and public education. With a deep understanding of this problem, it is hoped that research can provide solutions to increase accuracy in filling out birth certificates and maintain the integrity of the population administration system